Spinal cord detethering procedures in children: A 5 year retrospective cohort study of the early post-operative course. Issue 5 (May 2015) - Thuy, Matthew; Chaseling, Raymond; Fowler, Adam
Abstract Tethered spinal cord can cause neurological, orthopaedic and sphincteric problems in children and detethering surgery may prevent or reverse these problems. This 5 year retrospective cohort study aimed to review our experience of detethering surgery at The Children's Hospital at Westmead, Sydney, Australia, particularly examining the early post-operative complications of this procedure. Between 2007 and 2012, 61 children underwent 63 detethering procedures. The median age at detethering surgery was 1.4 years old (interquartile range: 0.7–5.6 years). Fifty-five children (90.1%) had lumbosacral procedures, 31 (50.8%) were asymptomatic from tethering, 11 (18.0%) had motor or gait disturbance, 11 (18.0%) sphincteric disturbance, eight (13.1%) lower limb orthopaedic deformities, eight (13.1%) scoliosis, six (9.8%) back or leg pain and two (3.3%) sensory disturbance. The most common tethering pathologies were spinal lipomas in 32 children (52.5%), filum abnormalities in 23 (37.7%), dorsal sinus tracts in eight (13.1%) and diastematomyelia in seven (11.5%). Twenty-six children (42.6%) had either a syrinx or central canal dilatation preoperatively. The most common complications were wound infection and cerebrospinal fluid leak. Six children (9.8%) required reoperation for wound issues and two patients (3.3%) required subsequent reoperation for cord retethering during the study period. There were no deaths and no new neurological deficits. Of the children with the above preoperative deficits, 26.7% were documented to have improvement or resolution of their symptoms post-operatively. The highest rate of improvement occurred in children with motor or gait disturbance (36.4%) or sphincteric disturbance (27.3%).